Gravity wave zoo: engaging citizen science to analyze atmospheric gravity wave activity over Poker Flat, Alaska - Karasinski, Tyler M.; Bossert, Katrina; Berkheimer, Jessica; Norrell, Jessica M.; Phillips, Sophie R.; Muñoz, Karina; Pautet, Pierre-Dominique (Frontiers in Astronomy and Space Sciences, 2026)
The Mesosphere and Lower Thermosphere (MLT) is a critical atmospheric region ranging from 80–140 km in altitude. A main driver of momentum transport, density perturbations, temperature variations, and background winds in this region are atmospheric gravity waves which are not well accounted for in many models of the thermosphere and near-space region. Additionally, global circulation models that do include GWs fail to resolve small-scale activity (<200 km). We utilize a hydroxyl (OH) airglow imager located in Poker Flat, Alaska (65°N 147°W) to leverage our active citizen science initiative, the Gravity Wave Zoo, expanding the breadth of available GW, aurora, and instability data over multiple seasons. We focus on a short-term study between 27 December 2023 and 4 February 2024 to statistically validate a subsample of this multi-year dataset, and report on recent Gravity Wave Zoo progress and accuracy, presenting a summary of overall participation and citizen classifications of GW, instability, and auroral events. We find citizen scientist classifications indicate GWs in 54.5%, aurora in 40.1%, and instabilities in 23.4% of subjects. We further propose future research directions enabled by this work and highlight the advantages of high temporal resolution data on the scale of weeks, months, and seasons.